Thrips Resistance Screening Is Coming of Age: Leaf Position and Ontogeny Are Important Determinants of Leaf-Based Resistance in Pepper - Visschers, Isabella G. S.; Peters, Janny L.; van de Vondervoort, Joep A. H.; Hoogveld, Rick H. M.; van Dam, Nicole M. (Frontiers in Plant Science, 2019)
Capsicum is a genus containing important crop species, many of which severely suffer from thrips infestation. Thrips feeding damages leaves and fruits, and often results in virus infections. Only few insecticides are still effective against thrips, underlining the importance of finding natural resistance in crops. Capsicum is a perennial plant which is usually cultivated for several months during which the fruits are harvested. From the young vegetative stage to the mature fruit bearing stage, the plants risk thrips infestation. Constitutive resistance to thrips over the entire ontogenetic development is therefore a key trait for more sustainable and successful cultivation of hot and sweet pepper. In addition to ontogeny, leaf position can affect the level of thrips resistance. Pest resistance levels are known to differ between young and old leaves. To our knowledge, no studies have explicitly considered ontogeny and leaf position when screening for constitutive resistance to thrips in Capsicum. In this study we analyze whether ontogeny and leaf position affect resistance to F. occidentalis and T. tabaci, in 40 Capsicum accessions, comprising five different species. Our results show that resistance to both thrips species in Capsicum varies with ontogenetic stage. We found no general pattern for ontogenetic variation in thrips resistance among the tested accessions. In addition, we found that thrips resistance is overall similar at different leaf positions within ontogenetic stage. This implies that resistance mechanisms, such as defense compounds, are constitutively present at sufficient levels on all leaf positions. Finally, we found that resistance to F. occidentalis and resistance to T. tabaci were not correlated. This indicates that thrips resistance in Capsicum is species-specific. Because of the variation in resistance over ontogeny, identifying Capsicum accessions with resistance over their entire lifespan is challenging. Accessions resistant to thrips in the flowering and fruiting stages, the crucial stages for fruit production, provide the most interesting leads for resistance breeding programs. For resistance screening, accounting for leaf position may be less of a concern. To identify the defense mechanisms responsible for thrips resistance, it is important to further analyze and compare resistant and susceptible accessions.